2010
DOI: 10.1177/1525740109356798
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Processes in the Speech of Jordanian Arabic Children With Cleft Lip and/or Palate

Abstract: The controlled and free speech of 15 Jordanian male and female children with cleft lip and/or palate was analyzed to account for the different phonological processes exhibited. Study participants were divided into three main age groups, 4 years 2 months to 4 years 7 months, 5 years 3 months to 5 years 6 months, and 6 years 4 months to 6 years 6 months, with bilateral or unilateral cleft lip and/or palate. Based on a productivity scale of a 20% or higher occurrence, results indicated the use of five productive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…As reported in previous studies (Al-Btoush, 2005;Al-Tamimi et al, 2011;Gerken, 1994;Kehoe & Steol-Gammon, 1997, 2001Levey & Schwartz, 2002;Pater, 1997;Raja, 2008), children tended to delete non-final and unstressed syllables.…”
Section: Cluster Reductionsupporting
confidence: 78%
See 1 more Smart Citation
“…As reported in previous studies (Al-Btoush, 2005;Al-Tamimi et al, 2011;Gerken, 1994;Kehoe & Steol-Gammon, 1997, 2001Levey & Schwartz, 2002;Pater, 1997;Raja, 2008), children tended to delete non-final and unstressed syllables.…”
Section: Cluster Reductionsupporting
confidence: 78%
“…The target of deletion is either the onset, the coda or the weak unstressed syllable in multisyllabic words (Dyson & Amayreh, 2000). Intriguingly, investigating syllable structure acquisition cross-linguistically proves the universality of weak/strong syllable rules indicating weak syllable deletion with preservation of the strong (stressed) syllables (Al-Btoush, 2005;Al-Tamimi et al, 2011;Gerken, 1994;Kehoe & Steol-Gammon, 1997, 2001Levey & Schwartz, 2002;Pater, 1997;Raja, 2008). By way of contrast, epenthesis refers to the addition/insertion of a segment (vowel/consonant) in order to meet the language syllable structure (Trask, 1996).…”
mentioning
confidence: 99%
“…The study also suggested that high level of education of speakers should not necessarily result in a higher approximation towards standard Arabic. The study's conclusions show that in Jordan, the two main factors that significantly affect how nonlocal, prestigious features are used are gender and social class (Tamimi, 2001).…”
Section: Review Of Literaturementioning
confidence: 94%
“…Different types of articulation errors such as nasalized stops, weak stops, devoicing errors, glottal, pharyngeal, palatal, and nasal substitutions are reported in the literature related to CLP speech [3,4,5,6]. Among these errors, nasal substitution for unvoiced stops is produced with highly altered glottal activity characteristics.…”
Section: Introductionmentioning
confidence: 99%